Solitary Animals: Introverts of the Wild - Stein, Joshua David; Ramsey, Dominique (New York : RISE, 2021)
"This lyrical, nonfiction text honors animals who live in solitude, in contrast to others who live in groups. Against a backdrop of the specific names of various animal tribes (a parade of elephants, a tower of giraffes, a dazzle of zebras), Stein shines a spotlight on those animals who go through life on their own. With nature at his back, Stein invites readers to draw strength and comfort from the behaviors of fellow mammals. Perfect for children who tend to be alone and their parents...as well as all children, who will be encouraged to respect the "natural" choices of their peers"--
Keywords: Swarming (Zoology) -- Juvenile literature; Animal behavior -- Juvenile literature; Swarming (Zoology); Animal behavior; Picture Book